Modulation of severe acute respiratory syndrome coronavirus (SARS-CoV-2) in receptor, innate immunity and drug antiviral candidate - Tarigan, Indra Lasmana; Arum, Kartika (Jurnal Teknologi Laboratorium, 2020)
The Coronavirus disease-19 (COVID-19) is a contagious acute respiratory infectious disease caused by SARS-CoV-2 as a global pandemic in 2020. This disease most spreads and causes some severe cases, even death in the world. The primary purpose of this review discusses the recent article that was published regarding COVID-19 genomic modulation, the mechanism of innate immunity, and the screening of anti-viral drug candidates, for treating COVID-19 patients. This review used the latest paper regarding COVID-19 with 63 journals with high impact factors such as Nature, The Lancet, Cells, International Journal of Biological Sciences, Mol Biol Methods. Journal of Microbiology, Immunology, and Infection, Nat. Rev. Microbiol, and other international journals indexed by Scopus, Elsevier, and Springer through in vivo and in vitro studies. The genomic of SARS-CoV-2 consist high similarly to coronaviruses family, albeit possessing a different pathway even has higher affinity, due to changing some nitrogen bases are supposed to have a significant effect on its pneumonia. Herein, we report review article an update on the recent literature of the COVID-19 modulation genome, mechanism of innate immunity, and medical literature. Moreover, we report anti-viral drugs that have been developed from synthetic drugs and medicinal compounds from plants. Several studies have been re-analyzed using in vitro, in vivo, and modelling using bioinformatics tools.